2018
DOI: 10.1002/jcp.27681
|View full text |Cite
|
Sign up to set email alerts
|

Formation and activation induction of primordial follicles using granulosa and cumulus cells conditioned media

Abstract: Fertility preservation of prepubertal girls subjected to invasive cancer therapy necessitates defining protocols for activation of isolated primordial follicles. Granulosa (GCs) and cumulus cells (CCs) play pivotal role in oocyte development. Although GCs and CCs share some similarities, they differ in growth factors production. The current study was conducted to evaluate the effects of GCs, CCs and their conditioned media on mice primordial follicles activation. One‐day‐old mice ovaries were subjected to 6‐da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…IMPM, intact mesenteric peritoneal membrane; DMPM, decellularized mesenteric peritoneal membrane. Asterisk, presence of the cells; arrow, collagen fibers before and after decellularization ECM-based scaffolds, 17 co-culture, 36,45 and different conditioned media derived from somatic cells 46 on in vitro follicular culture outcomes, there have, hitherto, been no studies on the use of DMPM as a scaffold and peritoneal mesothelial cells as supportive elements for in vitro development of ovarian follicles. In the current reported work, the peritoneum has been studied for the first time as a supportive structure for enabling in vitro growth of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMPM, intact mesenteric peritoneal membrane; DMPM, decellularized mesenteric peritoneal membrane. Asterisk, presence of the cells; arrow, collagen fibers before and after decellularization ECM-based scaffolds, 17 co-culture, 36,45 and different conditioned media derived from somatic cells 46 on in vitro follicular culture outcomes, there have, hitherto, been no studies on the use of DMPM as a scaffold and peritoneal mesothelial cells as supportive elements for in vitro development of ovarian follicles. In the current reported work, the peritoneum has been studied for the first time as a supportive structure for enabling in vitro growth of ovarian follicles.…”
Section: Discussionmentioning
confidence: 99%
“…Many earlier studies have also reported the positive effects of co-culture and conditioned medium on development of ovarian follicles. 10,36,46,59,60 These results may be related to the positive effects of the secretions of mesothelial stem cells (as LIF, EGF, TGFβ, Kitligand, and bFGF), 40 which suggests that these cells have secreted factors to promote in vitro growth of the follicles.…”
Section: Discussionmentioning
confidence: 99%
“…One-day-old mice ovaries were cultured for six days with conditioned media of GCs or CCs or co-cultured with these cells. Obtained results indicated that the conditioned medium of GCs could contribute to primordial follicle activation, probably due to downregulation of PTEN [147].…”
Section: Application Of Ovarian Follicular Stem Cells In Translational Medicinementioning
confidence: 95%
“…Therefore, the supernatant of cumulus-granulosa cells could be a useful IVF-enhancing tool [146]. Atrabi et al [147] investigated the influence of the conditioned medium of GCs and CCs on the activation of primordial follicles in mice. One-day-old mice ovaries were cultured for six days with conditioned media of GCs or CCs or co-cultured with these cells.…”
Section: Application Of Ovarian Follicular Stem Cells In Translational Medicinementioning
confidence: 99%
“…In prepubertal cancer patients, ovarian tissue could be cryopreserved and autotransplanted following recovery, but contamination of cryopreserved tissue with malignant cells and cancer reoccurrence are the risks pertaining to this technique (Bockstaele et al, 2012;Xiao et al, 2015;Amorim and Shikanov, 2016). Alternatively, cryopreserved ovarian tissue could be cultured to activate primordial follicles, which could further be used for in vitro production of embryos (Telfer et al 2008;Amorim and Shikanov, 2016;McLaughlin et al, 2018;Atrabi et al, 2019). Although in vitro activation of primordial follicles and in vitro production of metaphase II oocyte have been achieved successfully in postpubertal women (Telfer et al, 2008;McLaughlin et al, 2018), in vitro activation of primordial follicles in prepubertal girls remains to be defined (Telfer et al, 2008;Luyckx et al, 2013;Telfer and Zelinski, 2013).…”
Section: Introductionmentioning
confidence: 99%